HvHOX9, a novel homeobox leucine zipper transcription factor, positively regulates aluminum tolerance in Tibetan wild barley. (26th June 2020) - Feng, Xue; Liu, Wenxing; Dai, Huaxin; Qiu, Yue; Zhang, Guoping; Chen, Zhong-Hua; Wu, Feibo
Abstract : Root miRNA and RNA-Seq, coupled with BSMV-VIGS and MIFE, revealed that a novel transcription factor, HvHOX9, is essential in Al tolerance/accumulation via regulation of Al binding in cell wall and root growth. Abstract: Aluminum (Al) toxicity is the primary limiting factor of crop production on acid soils. Tibetan wild barley germplasm is a valuable source of potential genes for breeding barley with acid and Al tolerance. We performed microRNA and RNA sequencing using wild (XZ16, Al-tolerant; XZ61, Al-sensitive) and cultivated (Dayton, Al-tolerant) barley. A novel homeobox-leucine zipper transcription factor, HvHOX9, was identified as a target gene of miR166b and functionally characterized. HvHOX9 was up-regulated by Al stress in XZ16 (but unchanged in XZ61 and Dayton) and was significantly induced only in root tip. Phylogenetic analysis showed that HvHOX9 is most closely related to wheat TaHOX9 and orthologues of HvHOX9 are present in the closest algal relatives of Zygnematophyceae. Barley stripe mosaic virus-induced gene silencing of HvHOX9 in XZ16 led to significantly increased Al sensitivity but did not affect its sensitivity to other metals and low pH. Disruption of HvHOX9 did not change Al concentration in the root cell sap, but led to more Al accumulation in root cell wall after Al exposure. Silencing of HvHOX 9 decreased H + influx after Al exposure. Our findings suggest that miR166b /HvHOX9 play a critical role in Al tolerance by decreasing root cell wall Al binding and increasing apoplastic pH for Al detoxification in the root.